Information and communication management in university (on the example of the National University of Ostroh Academy and Silesian University in Katowice) - Yana Khodachuk; Yuliia Maslova (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2020)
The article deals with theoretical issues of information and communication management of the university. The role and impact of information and communication management on universities have been analyzed and researched on the example of Ostroh National University and Silesian University in Katowice. They are comparing the results obtained and making recommendations for improving the information and communication sphere in the universities.